A Report of Florida's Cancer History, Risk Factors, and Screening Behaviors: Data from the National Health Interview Survey - Laura A. McClure; Tainya C. Clarke; Cristina A. Fernandez; Kristopher L. Arheart; William G. LeBlanc; Lora E. Fleming; David J. Lee (University of North Florida, 2012)
To target populations at greatest risk ofdeveloping cancer, it is vital to understand the patterns ofrisk factors and screening behaviors along with cancer surveillance data. This study provides data on the prevalence of self-reported cancer history, can- cer risk factors, and cancer screening behaviors in Florida and compares them to rates in the rest ofthe U.S. Data were obtained from the National Health Interview Survey (NHIS), an annual, cross-sectional household survey of the U.S. civilian non-institutionalized population. We analyzed pooled data from the 2000 and 2005 Cancer Control Modules. Compared to the rest of the U.S., Floridians reported a lower prevalence of current smoking, risky drinking, and obesity, and a greater pre- valence of Prostate Specific Antigen (PSA) testing. However, Floridians reported a greater prevalence ofcancer history and a lower prevalence of physical activity, concern for sun protection, lifetime colorectal cancer screening, lifetime breast exam, life- time mammography screening, and lifetime and past year Pap test. The data indicate that Florida lags behind the rest of the U.S. in several areas, particularly cancer screening, and falls short ofthe Healthy People 2020 objectives for health behaviors and screening. These results provide information for key stakeholders and public health policy makers to effectively target Flor- ida residents at greatest risk for cancer and those not receiving recommended cancer screenings. This study also represents a model ofvaluable state-level evaluations that can be conducted using NHIS data. These types of analyses can provide a great- er understanding of state-level variations and lead to more effective public health interventions aimed at reducing cancer burden.